Administration of Islamic judicial system in ASEAN countries with particular reference to Malaysia - Wan Muhammad, Ramizah (LAP LAMBERT Academic Publishing AG & Co. KG, 2009)
Administration of Islamic Judicial system 15 the first book ever wfltten on the structure of shaflah courts In some selcted ASEAN countfles. ThIS book IS Intended for students. undergraduate and postgradute level and those who are working at Judiciary office as well as anybody Involved In legal fraternity and human fights organlstlons. Some thought provoking ISsues such as the Situation In Thailand and the Republic of the Phllipp,nes. The development of shaflah court In MalaySia from before and after the BfltISh ColonISation until the current state-status of shaflah court. MalaySia is given a good example of haVing correct structure and adequate syariah laws governing the MalaySian shaflah courts